Development of sol gel for UV and antibacterial protection / Wan Ahliah Bt Wan Ismail - Wan Ahliah, Wan Ismail (2016)

(untitled)
The current trend in coating industry is toward functional coating. The concept of functional building and even now the term ‘smart building’ have been the guide line for architects to diligently consider especially in high rise building. One particular fact considered is the maximum amount of light that enters the building. Thus, most high rise buildings incorporate glass panels that allow maximum amount of sunlight into the building. Whilst sunlight is free, the Ultra Violet (UV) can be hazardous. Thin film UV protective layer are regularly used on cars and glass panels are effective to block the unwanted UV rays but they have drawbacks. The films cling to the glass panels by adhesive between the plastic films and the glass and it will lose its functionality over some time and bubbles start to appear. The films need to be removed once these happened. Thus, films are definitely not an option to block unwanted UV rays in high rise building. Therefore, a clear coating that can bind to glass chemically is the best option for higher durability. In this research work, low temperature curing sol gel coating was developed for UV protective coatings. Glycidoxypropyl trimethoxy silane and amino propyl triethoxy silane were used as binders for high clarity with functionality of UV absorber coatings. Benzophenone has been used as the main UV absorber material in the coating layer and boron triflouride piperidine was used as the catalyst. It managed to block more than 99% of UV penetrating through the coating sample when coated on the blank float glass. Antibacterial or antimicrobial coatings also have created major demands in coating technology. In this research work, the antibacterial coating has been developed as the top coat of the coating that consists of low molecular weight methyl trimethoxy silane (136.22 g/mol) as the binder, N-propanol as the solvent and nano silver for antimicrobial agent. Nano silver was synthesised via precipitation method of silver nitrate and hydrazine hydrate as the reducing agent. The silver precipitates were added into the coating formulation and grinded using the ball milling. Nitric acid was added as a catalyst in the coating system. The coating was tested according to JIS Z 2801:2000 Antimicrobial product-Test for antimicrobial activity and Efficacy by SIRIM QAS Sdn Bhd. The antibacterial test result clearly shows the antimicrobial activity of the coated samples against Pseudomonas Aeruginosa, Staphylococcus Aureus and E-Coli.